UNLOCKING SUSTAINABLE E-COMMERCE SUCCESS IN THAILAND: A HOLISTIC MODEL OF DIGITAL CULTURE, INNOVATION, AND TECHNOLOGY ADOPTION - Siangchokyoo, nathajin; LEECHAROEN, Benjawan; SANGTHONG, Thaunjai (Asian Interdisciplinary and Sustainability Review, 2025)
This research investigates the critical factors driving sustainable e-commerce success in Thailand, emphasizing the synergistic role of digital organizational culture, innovation performance, digital integrated marketing communication (DIMC), and technology adoption. A mixed-methods approach was employed, combining quantitative analysis of survey data from 420 individuals with experience in purchasing from Thai e-commerce startups, and qualitative data from interviews with 15 key informants. Results indicate that digital organizational culture exerts the most significant influence, accounting for 44% of the variance in e-commerce success. Innovation performance and DIMC also exert significant direct and indirect effects, with technology acceptance playing a crucial mediating role. The validated structural equation model demonstrates a strong fit with the empirical data, indicating that these factors collectively explain a substantial portion of the variance in e-commerce success in Thailand. This research offers practical implications for e-commerce businesses, policymakers, and educators in Thailand. By prioritizing the development of a robust digital organizational culture, fostering innovation, implementing effective digital marketing strategies, and promoting technology adoption, organizations can enhance their competitiveness and achieve sustainable growth. The findings also provide valuable insights for policymakers seeking to create an enabling environment for e-commerce development in Thailand and similar Asian economies.